2013
DOI: 10.1016/j.jana.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Response to Edzi (AIDS): Malawi Faith-Based Organizations' Impact on HIV Prevention and Care

Abstract: African faith-based organization (FBO) leaders influence their members’ HIV knowledge, beliefs, and practices, but their roles in HIV prevention and care are poorly understood. This paper expands the work of Garner (2000) to test the impact of FBO influence on member risk and care behaviors, embedding it in the Theory of Planned Behavior. Qualitative interviews and quantitative surveys were collected from 5 FBOs (Christian and Muslim) in Malawi and analyzed using mixed methods. Contrary to Garner, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…This study adds significantly to the literature on engagement with faith-based organisations (FBOs) for effective HIV and AIDS prevention interventions in sub-Saharan Africa (SSA), an area of inquiry that is all too lacking (Lindgren et al, 2013;Olowu, 2015;Swidler & Watkins, 2017;Trinitapoli, 2009). It contributes to explicating impact of existing interventions, and addresses some major barriers that have hampered HIV-prevention efforts such as FBOs' anti-condom and abstinence-only messaging (Banda, 2017;Mukuka & Slonim-Nevo, 2006;Piot, Kazatchkine, Dybul, & Lob-Levyt, 2009;Rankin et al, 2008), emphasis on spiritual, rather than antiretroviral therapy (ART) for PLWH (Endeshaw et al, 2017;Kenworthy, Thomann, & Parker, 2018;Wanyama et al, 2007), fear of VCT (Jurgensen, Tuba, Fylkesnes, & Blystad, 2012) and stigmatisation of PLWH (Alubo, Zwandor, Jolayemi, & Omundu, 2010;Ansari & Gaestel, 2010;Rankin, Brennan, Schell, Laviwa, & Rankin, 2005;Williams, Haire, & Nathan, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study adds significantly to the literature on engagement with faith-based organisations (FBOs) for effective HIV and AIDS prevention interventions in sub-Saharan Africa (SSA), an area of inquiry that is all too lacking (Lindgren et al, 2013;Olowu, 2015;Swidler & Watkins, 2017;Trinitapoli, 2009). It contributes to explicating impact of existing interventions, and addresses some major barriers that have hampered HIV-prevention efforts such as FBOs' anti-condom and abstinence-only messaging (Banda, 2017;Mukuka & Slonim-Nevo, 2006;Piot, Kazatchkine, Dybul, & Lob-Levyt, 2009;Rankin et al, 2008), emphasis on spiritual, rather than antiretroviral therapy (ART) for PLWH (Endeshaw et al, 2017;Kenworthy, Thomann, & Parker, 2018;Wanyama et al, 2007), fear of VCT (Jurgensen, Tuba, Fylkesnes, & Blystad, 2012) and stigmatisation of PLWH (Alubo, Zwandor, Jolayemi, & Omundu, 2010;Ansari & Gaestel, 2010;Rankin, Brennan, Schell, Laviwa, & Rankin, 2005;Williams, Haire, & Nathan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A Trusted Messenger core principle is engaging through science to equip participants such as those interviewed in this study. Research elsewhere in SSA has shown that congregants are more likely to engage in HIVprevention behaviours when their religious leaders are equipped to discuss HIV and condom use (Lindgren et al, 2013;Múnoz-Laboy et al, 2011;Trinitapoli, 2009). Outcomes for congregants of leaders who participate in Trusted Messenger remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved HIV knowledge, the delay of sexual debut and decreased extra- and pre-marital sex is associated with religious commitment. 8 However, the strong condemnation of condom use potentially reduces knowledge, skills and the willingness of members to use condoms during risky sexual behaviour. 8 Furthermore, to remain members of good standing within the church, people have to behave in a proscribed manner or face discipline, meaning that the fear of falling out of favour with the church can positively affect their risk-taking behaviours whilst at the same time inhibit the disclosure of such behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective strategies were enhancing knowledge on HIV transmission to raise community awareness on HIV/AIDS transmission and prevention, abstaining from sexual risk behaviours and maintaining an exclusive relationship with a non-infected single sex partner by behaviour change communication and promotion of condom use [10,[15][16][17]. Regarding community-based organizations, Faith-based Organizations (FBO) influenced community members on their thoughts, beliefs, knowledge and practices in their lifestyles and behaviours including HIV/AIDS prevention [18,19]. McGrik [20] indicated that Muslim religious leaders in the Middle East and North Africa will be the key persons in addressing HIV/AIDS problems to move beyond AIDS awareness and behavioral change since they are respected role models for community members.…”
Section: Introductionmentioning
confidence: 99%